The association between financial performance, environmental characteristics, corporate governance mechanism and fraudulent financial reporting : evidence from Malaysian listed companies - Sulaiman, Mahanum (2014)
The collapse of a number of companies as a result of accounting manipulation by managers has raised serious questions about the effectiveness of the monitoring mechanism to protect investors’ interests and control managerial opportunistic behavior. This study examines financial performance, environmental characteristics and governance mechanisms on fraudulent financial reporting in Malaysia. Logit regression was performed on a sample of 36 fraud firms and 46 nofraud firms for the period of 2001 to 2009. The predictive accuracy of the logistic regression model is 66.1 percent. This study found that the greater the direct shares of the company owned by the board of director, the lesser would be the likelihood of fraudulent financial reporting. High stock ownership of board of director will increase the firm value, thus eliminating some of the inherent agency conflicts between the management and shareholders which is related to managers making decisions to benefit themselves rather than the shareholders. This study also found that the shorter the tenure of the CEO, the greater the tendency of the company to be involved in fraudulent financial reporting. Even though the internal control quality was found not to contribute significantly to fraudulent financial reporting, it was found that fraud companies, have lesser voluntary disclosure of internal control system compared to no-fraud companies. It is suggested that the Securities Commission and the Malaysian Institute of Accountants should encourage a greater level of voluntary disclosure of internal control system by all public listed companies, board of director to own greater number of shares in companies and CEO is encouraged to have a longer tenureship. Length of CEO tenureship is recommended to be 9 years or more as findings have shown that CEO with 9 years or more tenure is found to commit less in fraudulent financial reporting. This can also be included in Bursa Malaysia Listing Requirement (BMLR).